Characterization of EN-1078D, a poorly differentiated human endometrial carcinoma cell line: a novel tool to study endometrial invasion in vitro - Asselin Eric; Mes-Masso; Provencher Diane; Van Themsche Celine; Dery Marie-Claude (BMC, 2007)
Abstract Background To date, tools to study metastasis in endometrial cancers are insufficiently developed. The aim of this study was to characterize the cell line EN-1078D, a new endometrial carcinoma cell line derived from a metastasis to the ovary. Methods and Results Cells were characterized using cytology, transmission electron microscopy, karyotyping and morphological appearance in culture. Molecular features were determined by RT-PCR, Western Blot, FISH and sequencing. MTT proliferation assays were performed to investigate the sensitivity of EN-1078D to anticancer agents such as cisplatin and doxorubicin. Also, subcutaneous and intravenous injections in nude mice were done to test the tumorigenic and metastatic properties of EN-1078D cells. Our results indicate that EN-1078D cells express both oestrogen receptors isoforms (ER alpha and ER beta) and also low levels of progesterone receptor B (PR-B). In addition, this cell line expresses high levels of MMP-2 and MMP-14 mRNA, low levels of TIMP-1 and TIMP-2 transcripts and no detectable levels of MMP-9 mRNA. Moreover, all nude mice developed tumors by subcutaneous injections and cell invasion was observed in vitro in response to TGF-beta 3. Her-2/neu was not overamplified but mutations in the C-2 domain of PTEN gene as well as codon 12 of the K-Ras gene were found. Finally, EN-1078D shows sensitivity to drugs commonly used in chemotherapy such as cisplatin and doxorubicin: IC50 of 2.8 μM of cisplatin after 72 hours of exposure and 0.54 μM of doxorubicin after 48 hours. Conclusion Taken together, these results suggest that EN-1078D will be an excellent tool to study the properties of metastatic endometrial cancer cells in vitro and their regulation by sex steroids.